ANALYSIS OF INTERNAL CONTROL SYSTEM TO INVENTORY AT PT SUMBER ALFARIA TRIJAYA TBK IN PONTIANAK - B1031131040, Dwi Setya Nengsi (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Internal control in a developing company is currently very necessary in carrying out the company's operational activities. Inventory is the most valuable asset in a trading company, because inventory is the most active element in a trading company. One of the most important managerial functions in a company's operations is inventory control, because the physical inventory policy will be related to investment in current assets.In this study, the authors used case studies at PT Sumber Alfaria Trijaya, Tbk Branch Pontianak. With the aim to know and analyze the system of internal control to the inventory of goods applied by PT Sumber Alfaria Trijaya, Tbk Branch Pontianak. In the data analysis, the technique used is a qualitative analysis of the analysis of internal control methods of inventory.Based on the result of this research, it can be concluded that internal control system to inventory of goods in this company using internal control method that is evaluation of organizational structure, Flowchart, Internal Control Questionnaire (ICQ), and Complience Test in general is quite effective.Keywords: Internal Control System, Inventory, Organizational Structure Evaluation, Flowchart, Internal Control Questionnaire (ICQ), and Compliance Test.